Benefits of logistics centres categorization - Babic, Darko; Ivakovic, Morana; Průša, Petr (Univerzita Pardubice, 2008)
The process of globalization influenced multinational companies' production concentration into fewer locations. Market has demanded a new global logistics strategy. Since the end of 1980s global firms have been steadily reducing their number of national warehouses, consolidating them into regional distribution centres that serve a much wider geographical area. Logistics centers are challenged to otfer market a competitive and high quality categories of functions, enlarge their profitability, and limit environmental interference of their activities. ln this paper it is proposed a division of logistic centers in multiple categories, namely, starting from the realistic situation where the logistic centers stand today, imposes the need to explore the fort and consistent criteria for their categorization. The aim of the research is to determine logistics centres concept pointing at their need for categorization and to point out or to frame the benefits of logistics centre categorization. Conclusion of proposed article will be analysis of logistics centre benefits which will certainly atfect the change in the structure and organization of logistic centres that by improving the quality of operations and services achieve market competitive advantage.
Výhody kategorizace logistických center
Vorteile der Kategorisierung der logistischen Zentren